Definition5.2.1Diagonal Matrix
A square matrix D is called a diagonal matrix if \(d_{i j}\) = 0 whenever \(i \neq j\).
We have already investigated, in exercises in the previous section, one special type of matrix. That was the zero matrix, and found that it behaves in matrix algebra in an analogous fashion to the real number 0; that is, as the additive identity. We will now investigate the properties of a few other special matrices.
A square matrix D is called a diagonal matrix if \(d_{i j}\) = 0 whenever \(i \neq j\).
\(A = \left( \begin{array}{ccc} 1 & 0 & 0 \\ 0 & 2 & 0 \\ 0 & 0 & 5 \\ \end{array} \right)\), \(B= \left( \begin{array}{ccc} 3 & 0 & 0 \\ 0 & 0 & 0 \\ 0 & 0 & -5 \\ \end{array} \right)\), and \(I = \left( \begin{array}{ccc} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right)\) are all diagonal matrices.
In the example above, the \(3\times 3\) diagonal matrix \(I\) whose diagonal entries are all 1's has the distinctive property that for any other \(3\times 3\) matrix \(A\) we have \(A I = I A = A\). For example:
If \(A = \left( \begin{array}{ccc} 1 & 2 & 5 \\ 6 & 7 & -2 \\ 3 & -3 & 0 \\ \end{array} \right)\), then \(A I =\left( \begin{array}{ccc} 1 & 2 & 5 \\ 6 & 7 & -2 \\ 3 & -3 & 0 \\ \end{array} \right)\) and \(I A = \left( \begin{array}{ccc} 1 & 2 & 5 \\ 6 & 7 & -2 \\ 3 & -3 & 0 \\ \end{array} \right)\).
In other words, the matrix \(I\) behaves in matrix algebra like the real number 1; that is, as a multiplicative identity. In matrix algebra, the matrix \(I\) is called simply the identity matrix. Convince yourself that if \(A\) is any \(n\times n\) matrix \(A I = I A = A\).
The \(n\times n\) diagonal matrix \(I_n\) whose diagonal components are all 1's is called the identity matrix. If the context is clear, we simply use \(I\text{.}\)
In the set of real numbers we recall that, given a nonzero real number \(x\text{,}\) there exists a real number \(y\) such that \(x y = y x =1\). We know that real numbers commute under multiplication so that the two equations can be summarized as \(x y = 1\). Further we know that \(y =x^{-1}= \frac{1}{x}\). Do we have an analogous situation in \(M_{n\times n}(\mathbb{R})\)? Can we define the multiplicative inverse of an \(n\times n\) matrix \(A\text{?}\) It seems natural to imitate the definition of multiplicative inverse in the real numbers.
Let \(A\) be an \(n\times n\) matrix. If there exists an \(n\times n\) matrix \(B\) such that \(A B = B A =I\), then \(B\) is a multiplicative inverse of \(A\) (called simply an inverse of \(A\)) and is denoted by \(A^{-1}\)
When we are doing computations involving matrices, it would be helpful to know that when we find \(A^{-1}\), the answer we obtain is the only inverse of the given matrix. This would let us refer to the inverse of a matrix. We refrained from saying that in the definition, but the theorem below justifies it.
Remark: Those unfamiliar with the laws of matrices should go over the proof of Theorem 5.4.1 after they have familiarized themselves with the Laws of Matrix Algebra in Section 5.5.
The inverse of an \(n\times n\) matrix A, when it exists, is unique.
Let \(A\) be an \(n\times n\) matrix. Assume to the contrary, that \(A\) has two (different) inverses, say \(B\) and \(C\text{.}\) Then
Let \(A =\left( \begin{array}{cc} 2 & 0 \\ 0 & 3 \\ \end{array} \right)\) . What is \(A^{-1}\) ? Without too much difficulty, by trial and error, we determine that \(A^{-1}= \left( \begin{array}{cc} \frac{1}{2} & 0 \\ 0 & \frac{1}{3} \\ \end{array} \right)\) . This might lead us to guess that the inverse is found by taking the reciprocal of all nonzero entries of a matrix. Alas, it isn't that easy!
If \(A =\left( \begin{array}{cc} 1 & 2 \\ -3 & 5 \\ \end{array} \right)\) , the “reciprocal rule” would tell us that the inverse of \(A\) is \(B=\left( \begin{array}{cc} 1 & \frac{1}{2} \\ \frac{-1}{3} & \frac{1}{5} \\ \end{array} \right)\). Try computing \(A B\) and you will see that you don't get the identity matrix. So, what is \(A^{-1}\)? In order to understand more completely the notion of the inverse of a matrix, it would be beneficial to have a formula that would enable us to compute the inverse of at least a \(2\times 2\) matrix. To do this, we introduce the definition of the determinant of a \(2\times 2\) matrix.
Let \(A =\left( \begin{array}{cc} a & b \\ c & d \\ \end{array} \right)\). The determinant of \(A\) is the number \(\det A = a d - b c\).
In addition to \(\det A\), common notation for the determinant of matrix \(A\) is \(\lvert A \rvert\). This is particularly common when writing out the whole matrix, which case we would write \(\left| \begin{array}{cc} a & b \\ c & d \\ \end{array} \right|\) for the determinant of the general \(2 \times 2\) matrix.
If \(A =\left( \begin{array}{cc} 1 & 2 \\ -3 & 5 \\ \end{array} \right)\) then \(\det A = 1\cdot 5 -2\cdot (-3)=11\). If \(B =\left( \begin{array}{cc} 1 & 2 \\ 2 & 4 \\ \end{array} \right)\) then \(\det B = 1\cdot 4 -2\cdot 2=0.\)
Let \(A =\left( \begin{array}{cc} a & b \\ c & d \\ \end{array} \right)\). If \(\det A\neq 0\), then \(A^{-1} =\frac{1}{\det A}\left( \begin{array}{cc} d & -b \\ -c & a \\ \end{array} \right)\).
See Exercise 4 at the end of this section.
Can we find the inverses of the matrices in Example 5.2.8? If \(A =\left( \begin{array}{cc} 1 & 2 \\ -3 & 5 \\ \end{array} \right)\) then
The reader should verify that \(A A^{-1}=A^{-1}A = I\).
The second matrix, \(B\text{,}\) has a determinant equal to zero. If we tried to apply the formula in Theorem 5.2.9, we would be dividing by zero. For this reason, the formula can't be applied and in fact \(B^{-1}\) does not exist.
Remarks:
For the given matrices \(A\) find \(A^{-1}\) if it exists and verify that \(A A^{-1}=A^{-1}A = I\). If \(A^{-1}\) does not exist explain why.
No inverse exists.
\(A^{-1}=A\)
\(\left( \begin{array}{ccc} 1/3 & 0 & 0 \\ 0 & 2 & 0 \\ 0 & 0 & -1/5 \\ \end{array} \right)\)
For the given matrices \(A\) find \(A^{-1}\) if it exists and verify that \(A A^{-1}=A^{-1}A = I\). If \(A^{-1}\) does not exist explain why.
Let A and B be \(n\) by \(n\) invertible matrices.
Similarly, \((AB)\left(B^{-1}A^{-1}\right)=I\).
By Theorem 5.2.6, \(B^{-1}A^{-1}\) is the only inverse of \(AB\). If we tried to invert \(AB\) with \(A^{-1}B^{-1}\), we would be unsuccessful since we cannot rearrange the order of the matrices.
Let \(A =\left( \begin{array}{cc} a & b \\ c & d \\ \end{array} \right)\). Derive the formula for \(A^{-1}\).
\(1=\det I=\det \left(AA^{-1}\right)=\det A\text{ }\det A^{-1}\). Now solve for \(\det A^{-1}\).
Prove by induction that for \(n \geq 1\), \(\left( \begin{array}{cc} a & 0 \\ 0 & b \\ \end{array} \right)^n= \left( \begin{array}{cc} a^n & 0 \\ 0 & b^n \\ \end{array} \right)\).
Use the assumptions in Exercise 5.2.3.5 to prove by induction that if \(n \geq 1\text{,}\) \(\det \left(A^n\right) = (\det A)^n\).
Basis: \((n=1): \det A^1=\det A =(\det A )^1\)
Induction: Assume \(\det A^n=(\det A)^n\) for some \(n\geq 1\).
Prove: If the determinant of a matrix \(A\) is zero, then \(A\) does not have an inverse. Hint: Use the indirect method of proof and exercise 5.
Assume \(A=B D B^{-1}\)
Basis: \((m=1\)): \(A^{1}=A=B D^1 B^{-1} \) is given.
Induction: Assume that for some positive integer \(m\), \(A^m=BD^mB^{-1}\)